Sentidos de educação em disputa na política curricular para os cursos técnicos integrados ao nível médio do IFMT de Rondonópolis (MT) - Silva, Vinicius Batista da (2018)
This research lies in the line of research involving Teacher's Training and Public Educational Policies of the Post-Graduation Program in Education of the Federal University of Mato Grosso (UFMT), Campus of Rondonópolis, and it focuses on curricular policy for the Federal Institute of Mato Grosso (IFMT). Post-structural discourse discussions as a discursive practice, as Alice Casimiro Lopes and Elizabeth Macedo think, Chantal Mouffe's discussions of politics and democracy and Ball, Bowe and Gold's policy cycle approach constitute the theoretical-methodologies references that outline the study of politics on a post-structural basis. This study aims at analyzing the disputes to signify education in the political texts of the Federal Institute of Mato Grosso, in order to problematize the curricular policy rationale and its implications for what is understood by education, regarding the production of the Pedagogical Projects directed to High School integrated to Vocational Training Courses for the Rondonópolis Campus. Official documents of the Ministry of Education (MEC) and the IFMT (laws, resolutions, guidelines and pedagogical course projects) were analyzed, as well as practices instituted in the IFMT in addition to these texts. We problematized some discourses in the text of the Institutional Development Project (PDI) (2014-2018) of the IFMT to discuss how the signifiers education and quality are being addressed in the curriculum policy. We justify our choice for PDI as a point of departure with the fact that it is interpreted as a guiding document for the actions and production of the main policies of the Institution. The Apprentices formation demands are processed amidst the evocation of a certain tradition in the offering of Vocational Education interpreted in this document as a possibility to maintain a (good) quality education that is practiced since the old CEFET and more strongly characterized by instrumentalism. An important part of this research problem was to question how the High School Integrated to Vocational Education Courses were subjected to economic interests and the market production. It was possible to observe in the documents analyzed attempts to hegemonize meanings for education and quality for Vocational Education that assume an instrumental character of a more restricted formation of young people. Nevertheless, we argue that disputes concerning on hegemonizing meanings within this institution do not make it a space limited by negative or merely instrumental relations since the meaning it produces in this context runs off these attempts to control and take on forms of social inclusion, critical thinking and appreciation of differences, thus expanding the scope of education. We assume, therefore, that everything that is beyond the control of written texts is also part of the IFMT curricular policy, producing it with the active intervention of the subjects. It is important to highlight that there are always subjects actively deciding for the rational maintenance and overcoming and this allows to deconstruct the view of legal determinations as inexorable, while it is also possible to affirm that the discussion by another education remains open and urgent. The technicism that historically marks this professional education network is destroyed by broader visions of the differences that make up the curricula with living people which are affected in the educational process as they relate with life histories that promote bonds, new conflicts, and ethical commitments.